Plasmonic properties and photoinduced reflectance of topological insulator - Wang, Zilong (2018)
We report on linear and nonlinear infrared and plasmonic properties of chalcogenide crystal of the Bi-Sb-Te-Se family that was recently identified as a prospective platform for switchable broadband plasmonic devices.